2022
DOI: 10.3389/fncel.2022.987212
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial and microglial pathology in Down syndrome: Focus on Alzheimer's disease

Abstract: Down syndrome (DS) arises from the triplication of human chromosome 21 and is considered the most common genetic cause of intellectual disability. Glial cells, specifically astroglia and microglia, display pathological alterations that might contribute to DS neuropathological alterations. Further, in middle adulthood, people with DS develop clinical symptoms associated with premature aging and Alzheimer's disease (AD). Overexpression of the amyloid precursor protein (APP) gene, encoded on chromosome 21, leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 117 publications
1
4
0
Order By: Relevance
“…Consistent with the previous findings, we observed a decrease in DS patients’ oligodendrocytes in the frontal cortex and cerebellum. Microglia appeared to be more proliferative and active in DS populations in previous studies [ 53 , 57 ]. We revealed a significant increase in microglial cell proportions in the frontal cortex in DS patients.…”
Section: Discussionsupporting
confidence: 50%
“…Consistent with the previous findings, we observed a decrease in DS patients’ oligodendrocytes in the frontal cortex and cerebellum. Microglia appeared to be more proliferative and active in DS populations in previous studies [ 53 , 57 ]. We revealed a significant increase in microglial cell proportions in the frontal cortex in DS patients.…”
Section: Discussionsupporting
confidence: 50%
“…Given that reactive microglia is already detected early during neurodevelopment both in individuals with DS [ 18 , 19 , 20 , 21 ] and in DS mouse models [ 3 , 22 , 25 , 26 , 27 , 28 ], neuroinflammation could be explained by this increased microglial reactivity. In addition to that, it is also known that microglial reactivity increases with aging in DS [ 53 , 54 ], which might also contribute to the progression of DS neuropathology. However, whether microglial reactivity contributes to neuroinflammation or vice versa is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that investigated physical activity found that group exercise had positive effects on cognitive function 29,37 ; high levels of physical activity were associated with a reduced risk of behavioral decline 27 ; and sedentary behavior and activity were related to cognitive functioning and white matter development 34 . In addition, physical activity has been shown to activate glial cells (a type of cell that provides physical and chemical support to neurons and maintains their environment), which are important in cleaning up Aβ plaques within the brain 45,46 . It is believed that these glial cells become more dormant/inactive as one ages, and exercise can reactivate these glial cells in aging adults 46 .…”
Section: Discussionmentioning
confidence: 99%
“…34 In addition, physical activity has been shown to activate glial cells (a type of cell that provides physical and chemical support to neurons and maintains their environment), which are important in cleaning up Aβ plaques within the brain. 45,46 It is believed that these glial cells become more dormant/inactive as one ages, and exercise can reactivate these glial cells in aging adults. 46 Memory and attention measures were most sensitive to aging, and early markers of cognitive change in AD in DS included memory, language, and attention.…”
Section: Age-related Functional Changesmentioning
confidence: 99%